2021
DOI: 10.51847/qabgskl
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Bilineaster “Cotoneaster” on reducing bilirubin in neonates with jaundice -a triple-blind randomized clinical trial

Abstract: This is an open access journal, and articles are distributed under the terms of the Creative Commons Attribution-Non Commercial-ShareAlike 4.0 License, which allows others to remix, tweak, and build upon the work non-commercially, as long as appropriate credit is given and the new creations are licensed under the identical terms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…The level of bilirubin was checked every 24 hours for 72 hours after the initiation of treatment. The aforementioned study showed a significant difference in TSB between the two groups at 48 and 72 hours after the initiation of treatment (43).…”
Section: Herbal Agents For Treatment Of Neonatal Jaundicementioning
confidence: 82%
“…The level of bilirubin was checked every 24 hours for 72 hours after the initiation of treatment. The aforementioned study showed a significant difference in TSB between the two groups at 48 and 72 hours after the initiation of treatment (43).…”
Section: Herbal Agents For Treatment Of Neonatal Jaundicementioning
confidence: 82%
“…Their metaanalysis showed the positive effect of Cotoneaster manna on the treatment of neonatal jaundice. 28 Fakhri et al, assessed the preventive effect of purgative manna on neonatal jaundice. Cotoneaster (Shire Khesht) is most popular in Persian medicine.…”
Section: Discussionmentioning
confidence: 99%